Rising inequality in Asia and policy implications - Juzhong Zhuang; Ravi Kanbur; Changyong Rhee (Asian Development Bank Institute (ADBI), 2014)
This paper looks at the recent trends of rising inequality in developing Asia, asks why inequality matters, examines the driving forces of rising inequality, and proposes policy options for tackling high and rising inequality. Technological change, globalization, and market-oriented reform have driven Asia's rapid growth, but have also had significant distributional consequences. These factors have favored owners of capital over labor, skilled over unskilled workers, and urban and coastal areas over rural and inland regions. Furthermore, unequal access to opportunity, caused by institutional weaknesses and social exclusion, has compounded the impacts of these forces. All these combined have led to a falling share of labor income in national income, increasing premiums on human capital, and growing spatial disparity - all contributing to rising inequality. The three drivers of rising inequality cannot and should not be blocked, because they are the same forces that drive productivity and income growth. This paper outlines a number of policy options for Asian policy makers to consider in addressing rising inequality. These options, aiming to equalize opportunities and, thereby, reduce inequality, include efficient fiscal measures that reduce inequality in human capital, policies that work toward increasing the number and quality of jobs, interventions that narrow spatial disparity, and reforms that strengthen governance, level the playing field, and eliminate social exclusion.
Keywords: D63; O15; O53; 330; growth; globalization; inequality; governance